First report of Cotesia vanessae (Hymenoptera: Braconidae) in North America. Issue 5 (4th April 2014) - Hervet, V.A.D.; Murillo, H.; Fernández-Triana, J.L.; Shaw, M.R.; Laird, R.A.; Floate, K.D.
Abstract We report for the first time the occurrence of the well-known Eurasian and north African parasitoid Cotesia vanessae (Reinhard) (Hymenoptera: Braconidae) in North America. Specimens were reared from Chrysodeixis chalcites (Esper) and Trichoplusia ni (Hübner) (Lepidoptera: Noctuidae) recovered from several locations in southwestern Ontario, Canada, and detected by DNA sequencing from one Autographa californica (Speyer) (Lepidoptera: Noctuidae) in southern Alberta, Canada.